Neuroprotective Agents for Traumatic Brain Injury: Theoretical Therapy or the Future of Treatment? - Genis, Helen (The Meducator, 2013)
An increasing awareness of concussions in sports has led researchers to uncover that brain tissue damage is not instantaneous, but rather a delayed process following the initial injury. Recently, neuroprotective agents have been developed that will be administered after injury to reduce the effects of Traumatic Brain Injury (TBI). These agents include NMDA receptor antagonists that aim to interfere with excitotoxicity and reduce neuronal death. While these agents have improved learning and cognitive performance in animal models, their effects have not been as positive in clinical trials. Calpain inhibitors have also shown neuroprotective effects, and protect against axonal damage in the white matter of the brain. In the future, a better understanding of the cellular mechanisms of TBI will allow better development of neuroprotective agents for clinical use.